The Representation of Older People in East Asian Television Advertisements. (June 2017) - Prieler, Michael; Ivanov, Alex; Hagiwara, Shigeru
In this study, 432 television advertisements from Hong Kong, Japan, and South Korea were analyzed to determine their representations of older people. Findings demonstrate that in East Asian advertisements, older people are highly underrepresented, appear in major roles, mostly alongside younger people, and older men clearly outnumber older women. The other variables investigated (i.e., setting and product categories) led to no conclusive findings for the three societies. In short, our study, employing ethnolinguistic vitality theory to analyze television advertisements, demonstrates how East Asian societies greatly marginalize older people. Potential effects of such representations are discussed using social cognitive theory and cultivation theory.